THE COVERAGE OF MALAYSIAN SCHOLARLY JOURNALS BY INTERNATIONAL INDEXING AND ABSTRACTING SERVICES : AN ASSESSMENT OF THEIR VISIBILITY AND COMMON CHARACTERISTICS - Awang Ngah, Zainab (Malaysian Journal of Library and Information Science, 1997)
Studies the extent of coverage of the Malaysian scholarly journals by 23 major international indexing and abstracting services (12 services are in science, technology and medical (STM) disciplines and 11 are in the arts, humanities and the social sciences (AHSS)). A total of 54 Malaysian scholarly journals are identified (43 in the STM and 11 in AHSS disciplines) as being covered by these services. The journals and the articles which each contains therein are categorised as being â€œvisibleâ€ as the bibliographic information about the articles can be retrieved via published international databases on CD-ROMs or in printed versions of the indexes and abstracts which are available to most international researchers. A closer study of some â€œvisibleâ€ journals reveals that 15 (28%) are published by the University of Malaya, 8 (15%) by Universiti Pertanian Malaysia, 3 (5%) by other universities, 6 (11%) by associations and societies, and 22 (41%) by government agencies and others. The journals possess a number of common characteristics and features such as; regularity in publication frequency (the majority are published semi-annually); appropriate printing format and style; English as the publication medium; support from international reviewers who work closely with local editorial board members, and a high proportion of foreign papers.